Research of technological parameters of the concrete mixture compaction process in the conditions of construction of buildings and structures - BASARAB, Volodymyr; UMANETS , Iryna (Ways to Improve Construction Efficiency, 2025)
The article is devoted to the study of technological parameters of the process of compaction of concrete mix in the conditions of construction of buildings and structures. The relevance of rational selection of equipment for compaction of concrete mixtures, taking into account the most optimal technological parameters of the compaction process based on the specific conditions of building construction, was emphasized. A review of the main technological parameters of the process of vibratory compaction of concrete mix was conducted. The feasibility of researching and developing rational parameters of vibration equipment, taking into account the geometric parameters of the formwork, the properties of the concrete mix, and the amplitude-frequency regime of the vibration compaction process, was substantiated. The complex technological process of erecting monolithic concrete and reinforced concrete structures was considered and the physical model of vibration compaction of the concrete mix was described. The technology of compacting concrete mix using deep vibrators, surface vibrating plates, and mounted vibrators was described, and rational parameters for their application were given. The main technological parameters of the vibrocompaction process were given: geometric dimensions of the reinforced concrete structure being erected (height H, thickness B); structural features of the formwork (geometry, stiffness); properties of the concrete mix (density, stiffness, viscosity, vibroviscosity); location of the reinforcement and density of the reinforcement; parameters of the vibrocompaction equipment (amplitude X and frequency ω of the vibrations of the working body, power, geometry of the working body, amplitude-frequency spectrum of vibration energy transmission). The results of experimental studies of the propagation of stress waves and the phase shift angle at a concrete layer height of 1 m were presented. According to the results of experimental studies, it was established that the nature of the processes during the compaction cycle differs quantitatively and qualitatively - as compaction progresses, the stress-strain state in the mixture changes, and the spectrum of vibration oscillations also changes. Rational parameters and modes of vibration compaction were proposed based on the conditions for obtaining high quality monolithic structures and minimal energy consumption per unit of production.